COORDINATED RESEARCH PROJECT “DEVELOPMENT OF RADIOMETRIC METHODS AND MODELLING FOR MEASUREMENT OF SEDIMENT TRANSPORT - SEBASTIAN CALVO, Carlos (2021)
The first case study, namely Evaluation of leakages in Peruvian mining tail deposits by the aid of radiotracers, corresponds to the evaluation of leakages in two tailing deposits have been performed in a Peruvian Mining Company, in Cusco-Peru, through the injection of tritiated water as a proper tracer, and the use of isotope and chemical techniques, in order to confirm the existence of filtrations in the neighborhood of such tailing deposits. The objective of the study was to establish a cause-effect mechanism between the two mineral tailing deposits and its corresponded influence area, as probably receipt bodies of contamination. As a result of the intensive operation, it was established a cause-effect mechanism between the deposits and its corresponded influence area as a receipt bodies of contamination by tailing elements. The second case study, namely “Determination of flow velocities in groundwater by the aid of tracer techniques” corresponds to the evaluation of the groundwater resources in Ica Region at the southern Peru, and reports methodologies andtechniques developed for on-site artificial tracer aided measurements of groundwater flow velocities.